LATAR BELAKANG PEMAKAIAN GELAR “HAJI ” - Nanag Saptono (Kemendikbud, 2018)
The term of “Hajj” that applied to someone who has carried out the fifth pillar of Islam, at the time of the Prophet Muhammad was unknown. In the early period of Islam entrance in Indonesia, the term was also never been used. In some ancient texts, such as the Kronika Pasai and Sajarah Banten, the title was not used for figures that had alreadyperformed the hajj at first. The emergence of the title “Hajj” might be a symptom of retraditionalization. In pre-Islamic times, the term hajj was often used. In some inscriptions,this designation was often found. The problem that discussed in thispaper is why the Hajj title is applied to Muslims who have performed the hajj. The method that used in this research is through searching historical sources. It is known that the title of the hajj at that time was used for respectable matters. Retraditionalization symptoms in the term “Hajj”, intended to pay respect.